Application of Black Garlic-Based Bioconservants as Natural Preservatives for Chicken Meat Through Antibacterial Studies - Ellen Stephanie Rumaseuw; Monica Saptiningsih; Carissa Wityadarda (Postgraduate, University of Mataram, 2025)
Black Garlic has great potential as a natural bioconservant, because of anti-microbial activity, anti-inflammation, anti-allergic, anti- diabetic, and anti-cancer. However, research on its application as a bioconservant for chicken meat, particularly against multi-drug-resistant pathogens (E. coli, Salmonella sp., and Staphylococcus aureus) remains limited. The potential benefits of combining black garlic application with cold storage are also underexplored. This study investigates the potential of Black Garlic (BG) extract as a natural bioconservant to preserves broiler chicken meat by inhibiting bacterial growth and maintaining sensory quality. A Randomized design was used with six treatments applied: control, sodium benzoate (0.1%), and BG extract at 5% ,10%, 15%, and 20%. The samples were marinated for 30 minutes, wrapped, and stored at ± 10°C for seven days. Microbiological analysis showed that the 20% BG treatment effectively suppressed Salmonella to undetectable levels and significantly reduce E. Coli and Staphylococcus aureus, comparable to sodium benzoate. Lower concentrations were less effective, particularly against S. aureus. The measurements of pH indicated stabilization around 5.00-5.5 in BG-treated samples, with the 20% concentration exhibiting the strongest acidifying effect. Sensory evaluation by 26 panellists indicated that 15% BG improved the freshness of aroma but negatively affected color and texture at higher concentrations. Moisture content slightly increased in BG treatments, suggesting improved water retention. These findings demonstrate that black garlic extract, especially 15%-20%, can serve as a natural preservative for chicken. It is offer antibacterial protection while maintaining acceptable of sensory attributes. Moreover, the result highlights the potential of BG as a safer alternative to synthetic preservatives in the poultry industry.